2022
DOI: 10.3389/fped.2022.893002
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Kidney Transplantation—Can We Do Better? The Promise and Limitations of Epitope/Eplet Matching

Abstract: Kidney transplant is the optimal treatment for end-stage kidney disease as it offers significant survival and quality of life advantages over dialysis. While recent advances have significantly improved early graft outcomes, long-term overall graft survival has remained largely unchanged for the last 20 years. Due to the young age at which children receive their first transplant, most children will require multiple transplants during their lifetime. Each subsequent transplant becomes more difficult because of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…This relies on two fundamental principles: (1) the immune system's capacity to recognize and make antibodies for non-self-antigens, particularly epitopes on those antigens, while disregarding self-antigens and epitopes; (2) a small number of polymorphic amino acids near the center of the epitope, which largely establish epitope binding affinity. The evidence and the rationale for these postulates have been reported previously [2,6,7,11]. By inspecting amino acid sequences in donor and recipient alleles, HLAMatchmaker is able to pinpoint and quantify the differences between them.…”
Section: Hlamatchmaker Analysismentioning
confidence: 93%
See 2 more Smart Citations
“…This relies on two fundamental principles: (1) the immune system's capacity to recognize and make antibodies for non-self-antigens, particularly epitopes on those antigens, while disregarding self-antigens and epitopes; (2) a small number of polymorphic amino acids near the center of the epitope, which largely establish epitope binding affinity. The evidence and the rationale for these postulates have been reported previously [2,6,7,11]. By inspecting amino acid sequences in donor and recipient alleles, HLAMatchmaker is able to pinpoint and quantify the differences between them.…”
Section: Hlamatchmaker Analysismentioning
confidence: 93%
“…For solid grafts, the PIRCHE II describes the number of peptides of HLA proteins encoded in 2-5 exons of the donor's HLA but not in the recipient's. Similar to the naturally occurring thymic negative selection process, only candidate peptides proven absent in the patient's self-peptide background are considered allopeptides [2,13]. In a 2021 study, Unterrainer et al concluded that PIRCHE-II analysis could already be incorporated into kidney allocation algorithms providing an additional layer of compatibility assessment, particularly in cases where significant HLA incompatibilities exist between the donor and the recipient [14].…”
Section: Pirche Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…[28][29][30] While a full discussion of the strengths and weaknesses of each analysis approach is beyond the scope of this review, there are recent publications that provide excellent discussion of these points. 31,32 A study of 596 kidney transplant recipients compared the various scoring systems and found that each was highly correlated with HLA DR-and DQ-de novo DSA formation and that neither system was superior to the other (R 2 = .85-.96). 33 The key consideration when using these new tools is to understand their limitations, namely that the enumeration of the mismatches does not address the immunogenicity of the epitopes.…”
Section: Immunolog Ic Al Compatib Ilit Ymentioning
confidence: 99%
“…There are various software packages available to assess EMM, including HLAMatchmaker, PIRCHE‐II, Amino Acid Sequence Comparison, and Three‐Dimensional Electrostatic Mismatch (EMS‐3D), Table 1 28–30 . While a full discussion of the strengths and weaknesses of each analysis approach is beyond the scope of this review, there are recent publications that provide excellent discussion of these points 31,32 . A study of 596 kidney transplant recipients compared the various scoring systems and found that each was highly correlated with HLA DR‐ and DQ‐de novo DSA formation and that neither system was superior to the other ( R 2 = .85–.96) 33 .…”
Section: Immunological Compatibilitymentioning
confidence: 99%